2001
DOI: 10.1007/s00223-001-2028-4
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Osteoporosis in Patients with Chronic Liver Disease Prior to Liver Transplantation

Abstract: Osteoporosis is a common complication of liver transplantation. Its pathogenesis is multifactorial, but preexisting bone disease in patients with chronic liver disease is likely to play an important role. The aim of this study was to evaluate bone mineral density in adult patients with chronic liver disease prior to liver transplantation. A total of 243 consecutive patients (128 male, 115 female; mean age 51.1years) with chronic liver disease undergoing assessment for transplantation, were recruited over a 4-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 25 publications
4
62
1
5
Order By: Relevance
“…20 In a study of 243 consecutive patients with chronic liver disease undergoing assessment for liver transplantation, Ninkovic et al reported that 36.6% had osteoporosis according to WHO criteria 58 (a T score below -2.5) and bone mineral density was normal (T score above -1) in only 15.2%. 57 Importantly, men and women were equally affected and with the exception of increasing age and lower body weight in women, no independent risk factors were identified, emphasising the importance of bone mineral density measurements in these patients.…”
Section: Pre-existing Bone Diseasementioning
confidence: 93%
“…20 In a study of 243 consecutive patients with chronic liver disease undergoing assessment for liver transplantation, Ninkovic et al reported that 36.6% had osteoporosis according to WHO criteria 58 (a T score below -2.5) and bone mineral density was normal (T score above -1) in only 15.2%. 57 Importantly, men and women were equally affected and with the exception of increasing age and lower body weight in women, no independent risk factors were identified, emphasising the importance of bone mineral density measurements in these patients.…”
Section: Pre-existing Bone Diseasementioning
confidence: 93%
“…A rate from 12 % to 55% of patients may have osteoporosis before liver transplantation as a result of their underlying chronic hepatic disease (37). It has been demonstrated that the bone health before transplantation may be a predictive factor of bone loss and fracture after the liver is transplanted (38).…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Low-energy fractures occur in 14-21% of patients with chronic hepatitis and patients with liver cirrhosis and 45% in patients with end-stage liver failure referred for liver transplant [17]. Osteoporosis occurred in 36.6% and osteopenia in 48.1% of a group of 243 patients with chronic liver disease in the preparatory period for liver transplant [18]. After liver transplantation, an osteoporotic bone is exposed to additional risks, even to the immunosuppressive therapy the patient has to take for life.…”
Section: Osteoporosis In Liver Diseasesmentioning
confidence: 99%